Rethinking Pro Growth Monetary Policy in Africa: Monetarist versus Keynesian Approach - (:unkn) unknown (My University, 2013)
The relative positive economic growth experienced by most African countries in the recent decade has come with insufficient demand stimulation. The concern of poverty at the forefront of economic policy, the need for inclusive growth and sustainable development, inter alia, brings forward the inevitable question of the monetary policy responsibility. Accordingly, the monetarist theory that focuses on price stability inherently neglects the demand stimulation aspect of economic prosperity. Since the mid 1980s, the monetarist school driven by its central aim of fighting inflation and maintaining credibility in markets and economic agents has been priority for monetary authorities (especially in Africa). To this effect, while good results in terms of inflation targeting has been achieved in many African countries; economic growth has sometimes been low. Hence, in light of the above, using a statistical and theoretical debate method, the Credible Monetary Policy (CMP)1 paradox is traceable to Africa. Accordingly, with the promising economic environment in Africa, we recommend the promotion of a monetary policy oriented toward improving economic growth under the constraint of price stability.
Keywords: African Research